Dream big starring Olivia - Falconer, Ian 1959- (Andrews McMeel, 2006)
Olivia dreams big. Whether she's taming a circus lion or building a sandcastle as tall as the Empire State Building, her boundless imagination and courageous spirit are an inspiration to young and old...